Drug utilization profile in adult patients with refractory epilepsy at a tertiary referral center - Priscila de Freitas-Lima; Andre de Oliveira Baldoni; Veriano Alexandre; Leonardo Regis Leira Pereira; Americo Ceiki Sakamoto (Arquivos de Neuro-Psiquiatria)
Objective To evaluate the utilization profile of antiepileptic drugs in a population of adult patients with refractory epilepsy attending a tertiary center. Method Descriptive analyses of data were obtained from the medical records of 112 patients. Other clinical and demographic characteristics were also registered. Results Polytherapies with ≥3 antiepileptic drugs were prescribed to 60.7% of patients. Of the old agents, carbamazepine and clobazam were the most commonly prescribed (72.3% and 58.9% of the patients, respectively). Among the new agents, lamotrigine was the most commonly prescribed (36.6% of the patients). At least one old agent was identified in 103 out of the 104 polytherapies, while at least one new agent was prescribed to 70.5% of the population. The most prevalent combination was carbamazepine + clobazam + lamotrigine. The mean AED load found was 3.3 (range 0.4–7.7). Conclusion The pattern of use of individual drugs, although consistent with current treatment guidelines, is strongly influenced by the public health system.